2008
DOI: 10.1590/s0100-879x2008000900014
|View full text |Cite
|
Sign up to set email alerts
|

Training-related changes in the R-R interval at the onset of passive movements in humans

Abstract: The aim of the present study was to determine whether training-related alterations in muscle mechanoreflex activation affect cardiac vagal withdrawal at the onset of exercise. Eighteen male volunteers divided into 9 controls (26 ± 1.9 years) and 9 racket players (25 ± 1.9 years) performed 10 s of voluntary and passive movement characterized by the wrist flexion of their dominant and non-dominant limbs. The respiratory cycle was divided into four phases and the phase 4 R-R interval was measured before and immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This aspect is clinically interesting, as previous studies with the latter protocol have demonstrated that the rapid movement of the legs or arms 39 and even the bending of wrists 40 is capable of inducing a rapid and sharp increase in heart rate and also the SBP 41 and that this response can be completely abolished by selective pharmacological blockade with atropine 42 , characterizing the mechanism of vagal inactivation as responsible for the response.…”
Section: Discussionmentioning
confidence: 90%
“…This aspect is clinically interesting, as previous studies with the latter protocol have demonstrated that the rapid movement of the legs or arms 39 and even the bending of wrists 40 is capable of inducing a rapid and sharp increase in heart rate and also the SBP 41 and that this response can be completely abolished by selective pharmacological blockade with atropine 42 , characterizing the mechanism of vagal inactivation as responsible for the response.…”
Section: Discussionmentioning
confidence: 90%
“…There are several mechanisms that may contribute to the increase in HR observed at the onset of volitional exercise, including central command (i.e. feed‐forward control) (Eldridge et al 1985; Williamson et al 2006), sympathetic stimulation (Warner & Cox, 1962; Robinson et al 1966; Rowell, 1986), cardiac vagal withdrawal (Fagraeus & Linnarsson, 1976; McMahon & McWilliam, 1992; Vianna et al 2008) and muscle afferents (i.e. feed‐back control) (Coote et al 1971; Stebbins et al 1988; Adreani et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The sensory component of the EPR comprises group III and IV skeletal muscle afferents that respond to both mechanical (i.e., muscle mechanoreflex) and metabolic (i.e., muscle metaboreflex) stimuli (32). In humans, the muscle mechanoreflex can be activated by mechanical stretch (10,24) or passive movement (43,54,57,58); however, its effects on cardiovascular responses appear small and transient. In contrast, muscle metaboreceptors are paramount in generating the reflex increases in sympathetic outflow during exercise in normal physiological states (18,20,21,32,48).…”
Section: Introductionmentioning
confidence: 99%